Dynamics of soil liming materials broadcast on a thaptoargic hapludoll soil in Argentina - Vázquez, Mabel (2013)
Fil: Vázquez, Mabel. Universidad Nacional de La Plata. Facultad de Ciencias Agrarias y Forestales; Argentina